2016
DOI: 10.1039/c6cc03289c
|View full text |Cite
|
Sign up to set email alerts
|

2-Methylresorcinarene: a very high packing coefficient in a mono-anion based dimeric capsule and the X-ray crystal structure of the tetra-anion

Abstract: Mono- and tetra-deprotonated 2-methylresorcinarene anions ( and ) as their trans-1,4-diammoniumcyclohexane inclusion complexes are reported. The mono-anion forms a fully closed dimeric capsule [·H2O·MeOH]2(2-) with a cavity volume of 165 Å(3) and as the guest with an extremely high packing coefficient, PC = 84.2%, while the tetra-anion forms a close-packed structure with two structurally isomeric tetra-anions and with a 50 : 50 ratio in the crystal lattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…It has been reported that for optimal encapsulation, the ratio of the guest volume to the host cavity volume should fall within the 55% ± 9% range . Although packing coefficients exceeding this target range have been observed in some cases, especially when there are strong interactions and a good geometric match between the host and the guest, as a general rule high encapsulation ratios are correlated with novel host–guest properties. , To the best of our knowledge, the packing coefficient for 3 ⊃TEA + matches the highest value reported to date and could reflect the conformational changes that accompany guest binding (e.g., bending of the triphenyltriazine planes as seen in the solid state structure discussed above). In other words, the high occupancy ratio seen for 3 ⊃TEA + may benefit from a kind of “induced fit” binding phenomenon. , …”
Section: Resultssupporting
confidence: 59%
“…It has been reported that for optimal encapsulation, the ratio of the guest volume to the host cavity volume should fall within the 55% ± 9% range . Although packing coefficients exceeding this target range have been observed in some cases, especially when there are strong interactions and a good geometric match between the host and the guest, as a general rule high encapsulation ratios are correlated with novel host–guest properties. , To the best of our knowledge, the packing coefficient for 3 ⊃TEA + matches the highest value reported to date and could reflect the conformational changes that accompany guest binding (e.g., bending of the triphenyltriazine planes as seen in the solid state structure discussed above). In other words, the high occupancy ratio seen for 3 ⊃TEA + may benefit from a kind of “induced fit” binding phenomenon. , …”
Section: Resultssupporting
confidence: 59%
“…The combined volume of two ID guests (74%) significantly exceeded the value of 55 ± 9% of the host cavity volume (409 Å 3 ), which Rebek showed a while ago afforded optimal guest binding in solution [50,51]. However, a crystalline sponge experiment was performed under highly forcing and non-equilibrium conditions using a large excess of the guest; we [48] and others [52][53][54] have observed packing coefficients for guests inside supramolecular host cavities of >80% when favourable interactions such as π-stacking between multiple guests and favourable interactions between guests and the cage interior surface result in a particularly compact guest array. In dilute solution-the conditions under which guest binding is normally evaluated-we can imagine that for this reason, the second binding constant K 2 would be substantially smaller than the first binding constant K 1 , in which case, the single-guest binding would dominate the solution speciation behaviour [48].…”
Section: Resultsmentioning
confidence: 82%
“…While hitherto reported resorcinarene‐based inclusion complexes achieve very high packing coefficients of up to 84 % via strong ionic host‐guest interactions, [31] hemicarceplex 1 ⋅ chloroform 2 utilizes the hemicarcerands adaptivity and the guest‘s mobility, matching electrostatics and sterics of host and guest molecules to obtain a packing coefficient of 91 %.…”
Section: Resultsmentioning
confidence: 99%